2021
DOI: 10.1002/celc.202100341
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Hydrogen Peroxide Biosensor Based on Tobacco Peroxidase Immobilized on p‐Phenylenediamine Diazonium Cation Grafted Carbon Nanotubes: Preventing Fenton‐like Inactivation at Negative Potential

Abstract: Herein, we present a novel electrode platform for H 2 O 2 detection based on the immobilization of recombinant Tobacco Peroxidase (r-TOP) onto graphite electrodes (G) modified with p-phenylenediamine (p-PD) diazonium cation grafted multiwalled carbon nanotubes (MWCNTs). The employment of both p-phenylenediamine moieties and covalent cross-linking by using glutaraldehyde allowed us to enhance the sensitivity, stability, and selectivity toward H 2 O 2 detection, as well as preventing enzyme inactivation due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…In addition, as summarized in Table 3, the higher stability of the NCPs and stronger oxidizing properties of hydrogen peroxide in acidic medium are reflected in the higher sensitivity, lower detection limit, and wider working concentration range obtained at pH 3 than 7.4. The LDL H2O2 of the NCPs is comparable with that of the biosensors based on various plant peroxidases [34,63]. It can be concluded that the electrocatalysis of hydrogen peroxide reduction by Mn-PB and PB NCPs is reminiscent of their peroxidase-like catalytic substrate oxidation and the cytotoxicity of iron oxide in terms of the destructive action of the produced hydroxyl radicals.…”
Section: Resultsmentioning
confidence: 62%
“…In addition, as summarized in Table 3, the higher stability of the NCPs and stronger oxidizing properties of hydrogen peroxide in acidic medium are reflected in the higher sensitivity, lower detection limit, and wider working concentration range obtained at pH 3 than 7.4. The LDL H2O2 of the NCPs is comparable with that of the biosensors based on various plant peroxidases [34,63]. It can be concluded that the electrocatalysis of hydrogen peroxide reduction by Mn-PB and PB NCPs is reminiscent of their peroxidase-like catalytic substrate oxidation and the cytotoxicity of iron oxide in terms of the destructive action of the produced hydroxyl radicals.…”
Section: Resultsmentioning
confidence: 62%
“…On the other hand, the presence of CNTs in DRP-110CNT/ Tv Lac + GA significantly favored the stability of the catalytic activity over time up to 400 mM of catechol, shown in Figure 4 b in grey. The well-known high porosity of CNTs plays a dramatic role in the physical adsorption mechanism and in the immobilization stability [ 42 , 43 , 44 , 45 , 46 ]. However, the catalytic current increased slower than with the DRP-110GNP/ Tv Lac + GA electrode, an index of lower sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the presence of CNTs in DRP-110CNT/TvLac + GA significantly favored the stability of the catalytic activity over time up to 400 mM of catechol, shown in Figure 4b in grey. The well-known high porosity of CNTs plays a dramatic role in the physical adsorption mechanism and in the immobilization stability [42][43][44][45][46]. However, the catalytic current increased slower than with the DRP-110GNP/TvLac + GA electrode, an index of lower sensitivity.…”
Section: Resultsmentioning
confidence: 99%